Political and Legal Basis of the Conjugation of the Eurasian Economic Union and Silk Road Economic Belt: Formation Process and Perspectives of Co-operation - Ya. Glittova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2019)
As the title implies the article deals and analyse the cooperation processes of the conjugation of the Eurasian Economic Union (EAEU) and the Silk Road Economic Belt.The purpose of the article is to identify mechanism of the conjunction of the EAEU and Silk Road Economic Belt. To conduct the research and generate results, authors applied document analysis method. The object of the study is the mechanism of the conjugation of the EAEU and Silk Road Economic Belt.The subject of the research is Russian-Chinese bilateral relations, political and economic aspects and the normative legal base between the EAEU and China. Dependent variables of the research: normative legal framework, political and diplomatic relations, trade and investment cooperation, transport and logistics corridors, industry network, geopolitical constituent, Russian-Chinese relations. Independent variables of the research: the EAEU integration process, agreements between EAEU and Vietnam, Iran, India.It is analysed and stressed the vital role in the intensification bilateral relations and in the formation of normative legal base between the EAEU member states and the People’s Republic of China (PRC), as well as between the Russia and the PRC in creating favorable conditions to strengthen conjugation of the EAEU and the Silk Road Economic Belt.The article demonstrates a high level of Russian-Chinese relations in strategic areas of cooperation, a large complex of normative legal base, the importance of developing transport infrastructure and industrial network, the significance of increasing turnover including improving the investment environment.It is highlighted a crucial role of the Eurasian Economic Commission in creating a normative legal base of the conjugation mechanism of the EAEU and Silk Road Economic Belt in accordance with its competencies. One of the key issues of the article is an important role of the diplomatic and political mechanism of member states´ interaction in implementing the conjugation of the EAEU and the Silk Road Economic Belt. It is analysed the substantial role of nuclear energy as one of the major areas of economic cooperation between Russia and China, as well as one of the main factors for strengthening the conjunction of the EAEU and the Silk Road Economic Belt.It is underlined dynamism of cooperation of the conjugation. It is stressed the key role of the number of signed normative legal documents as well as a wide range of fields of interaction between the EAEU and the Silk Road Economic Belt. It is established that for the further cooperation is necessary to activate and intensify legal framework between the member states of the EAEU and China. It is shown that listed factors indicate positive perspectives for further cooperation of the conjunction.